WORKFORCE Description and development of a nurse-led cardiac assessment team. Issue 1 (2020) - Kwok, Chun Shing; Naneishvili, Tamara; Curry, Sonia; Aston, Charlotte; Beeston, Michelle; Chell, Sarah; Cripps, James; Gunter, Bob; Jackson, Debbie; Thomas, Diane; Jones, Angela; Bethell, Helen; et al.
No abstract available